DAMPAK LINGKUNGAN PENAMBANGAN SILIKON PROSES PEMURNIAN, PABRIKASI SEL/MODUL, PEMBANGKITAN DAN DEKOMESIONING SISTEM FOTOVOLTAIK - Lubis, Abubakar (Jurnal Teknologi Lingkungan, 2006)
The most important part is manufacturing since PV modules areproduced under very height energy consumption characteristic.Photovoltaic energy production is suppose to be an environmentallyfriendly energy system with no emissions and no waste production, cleanand noiseless but ins important to ensure that manufacturing is not goingto be more harmful for the environment than operation advantages. Then itis very important to know if the product is going to be economically andenvironmentally viable for the overall life cycle. For the manufacturingprocesses environmental impact, three different studies have been carriedout: Energy Analysis, Energy Related Emissions Analysis and Materialflow analysis.Operation. Advocates of renewable solar system argue thatduring operation the environmental impact of this technology is minimal incomparison with other form of renewable energies. Decommissioning. At theend of the lifetime of the modules, they must be dispose in a sensitiveway. At the moment there are no many option for recycle the siliconwafer. Aluminum frames can be recycled separately in the same wayas this material normally is, glass could be recycle i technologies would exist to separates the glass from the adherent EVA and othermodule components.